Afiksasi Kata Kerja Masa Lampau dalam Bahasa Arab dan Bahasa Indonesia; Analisis Kontrastif - Bashirotul Hidayah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
The problem of linguistic in studying Arabic for non-Arabic (Indonesian students), especially in the case of affixation or in Arabic known as Tasrif. This is a fundamental difference in the process Tasrif both in Arabic and Indonesian. Competence to compare the two languages is a must for teachers of Arabic, so that the obstacles encountered can be solved immediately. So that the learning process can be run effectively and efficiently.